The profile distribution of minerals within the solonetz in Yergeni - N. P. Chizhikova; N. B. Khitrov; E. B. Varlamov; N. A. Churilin (Бюллетень Почвенного института им. В.В. Докучаева, 2018)
The mineralogical composition of clay (10 mm) of light fine solonchakous solonetz strongly salinized by sulphate-chloride highly calcareous with gypsum content light clay-light clay loamy-heavy clay loamy on the loess like clay loams (Chromic Calcic Gypsic Endosalic Solonetz (Albic, Episiltic, Epiclayic, Endoloamic, Columnic, Cutanic, Differentic)) located on the highest eastern part of Yergeni upland at about 70 km in the north from Elista (Kalmykia). The investigated profile is formed on the homogenous aeolian clay loam deposits. The elluvial and illuvial distribution of clay in the solonetz profile is accompanied by the changes in the ballance of clayey minerals in the above solonetzic and solonetzic horizon. The following processes occurwithin the SEL above solonetzic elluvial horizon: (1) the destruction of the mixed layer formations of mica-smectitic type with the residual preservation of mixed-layer chlorite-vermicullites in clay; (2) the relative accumulation of trioctahedrical micas within the clay; (3) the outflow of the clayey (10 mm), plagioclases (from 10-13% to 21-28%), potassium feldspars (from 9-13% to 15-20%), and the decrease of micas content (from 30-40% to 4-9%). The minerals distribution within the silt fraction along the solonetzes profile is relatively homogenous.